Natural resources and economic growth: A meta-analysis - Tomas Havranek; Roman Horváth; Ayaz Zeynalov (Institut für Ost- und Südosteuropaforschung (IOS), 2015)
An important question in development studies is how abundance of natural resources affects long-term economic growth. No consensus answer, however, has yet emerged, with approximately 40% of empirical papers finding a negative effect, 40% finding no effect, and 20% finding a positive effect. Does the literature taken together imply the existence of the so-called natural resource curse? In a quantitative survey of 402 estimates reported in 33 studies, we find that overall support for the resource course hypothesis is weak when potential publication bias and method heterogeneity are taken into account. Our results also suggest that three aspects of study design are especially effective in explaining the differences in results across studies: 1) including an interaction of natural resources with institutional quality, 2) controlling for the level of investment activity, and 3) distinguishing between different types of natural resources.
urn:nbn:de:101:1-201603225129
Keywords: Q30; O13; C51; 330; natural resources; economic growth; institutions; publication selection bias; metaanalysis